Confronting femicide: multidisciplinary perspectives from Puerto Rico - Natarajan, Nalini (Palgrave Pivot, 2025)
This book explores the idea that the extreme criminal action that constitutes femicide must be explored not in isolation, but in the context of gender cruelty and misogyny in society. It focuses on the island of Puerto Rico as a case study. The chapters cover topics such as Afro-feminist and anti-racist grassroots work, transfeminist justice, and the role of art in resistance. This volume is essential reading for scholars of gender studies, activists fighting against gender-based violence, and anyone interested in understanding the complex layers of oppression that lead to such extreme manifestations of violence. It invites readers to think through critical questions about justice, resistance, and the power of community organizing. Nalini Natarajan is Professor of English at the University of Puerto Rico, Rio Piedras, Puerto Rico. She is the author of six books, including Atlantic Gandhi: The Mahatma Overseas (2012) and The Unsafe Sex: The Female Binary and Public Violence against Women (2016). Her latest book is titled Romance and Power in the Hollywood Eastern (Palgrave, 2021).